Atlas of minimally invasive facelift : facial rejuvenation with volumetric lipofilling - Serra-Renom, Jose Maria; Serra-Mestre, Jose Maria (Springer, 2016)
This atlas provides a concise overview of the principle of fat grafting and its clinical applications to treat aging in the central areas of the face in a minimally invasive manner. The authors start with a short description of the anatomical basis of facial aging and by presenting current facial rejuvenation techniques. Here the emphasis is on the process of harvesting and preparing macro-, micro-, intradermal and nano-fat for injection. Thanks to the book's numerous illustrations and short descriptions, readers will find valuable information on where and how to inject the fat combined with the authors' individual techniques and refinements. Aging is a major issue in today's society. Facial rejuvenation procedures seek to enhance the final outcome and durability of surgery and to minimize drawbacks. The current trend is to use less invasive methods requiring fewer incisions, which produce more natural-looking results. This atlas shows the authors' personal techniques to help achieve that goal.